The past and future of social group work in Germany: contributions of Louis Lowy - Gardella, Lorrie Greenhouse (Social Work with Groups, 2021)
Louis Lowy (1920 to 1991), the international social work educator, remembered surviving the Holocaust as a formative professional experience. After joining the faculty of Boston University School of Social Work, Lowy returned to Germany every summer for 20 years to help restore social work education. This SPARC project, “The Past and Future of Social Group Work in Germany: Contributions of Louis Lowy,” was proposed in collaboration with Klaus-Martin Ellerbrock and the German Chapter of IASWG at the height of the 2015 global refugee crisis, when Germany admitted more than one million refugees. The purposes of the project were to encourage ongoing international scholarship on the implications of Lowy’s teachings for social work with groups; to facilitate research and writing from an international perspective on group work with migrants and other disenfranchised populations; and to foster international collaborations among group workers in the spirit of Louis Lowy. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.swk; peer-reviewed